Sexual Dimorphism in Permanent Maxillary and Mandibular Canine of Medical Students in Gandaki Medical College, Nepal - Shrestha, Bijayata (Birat Journal of Health Sciences, 2019)
Introduction: Gender determination is important for identification in forensic practice. Odontometrics plays an important role in sex determination in young individuals where secondary sexual characters are yet to be developed.Objective: The objective was to re-evaluate the previous finding of the sexual dimorphism in Mesiodistal (MD) and Buccolingual (BL) dimension of maxillary and mandibular canine in the study population being Medical Students of Medical College in province 4 of Nepal.Methodology: This is a cross sectional study conducted on the study cast of 40 male and 40 female medical students of academic year 2017/18 of Gandaki Medical College, Nepal, of age group 18-24 from October to December 2017. The MD and BL dimensions of all the four canines were measured using digital vernier's caliper. Data were compared using descriptive statistics, student's t-test and paired sample t test. P